Integrating Policies, Practices and E-Marketing Examination on Customer Satisfaction Capability for Scholarly Publishing in Malaysian Public Universities - Ali, R.; Bani Hashim, A.Y. (International Journal of Human and Technology Interaction (IJHaTI), 2017)
Due to its depleting importance, scholarly publishing grew unpopular in a weak market where business is done in a conventional way. University Press uses e-marketing to promote academic publication. As a widely accepted strategy, e-marketing has been used by many organizations around the world to market their daily businesses. Various studies have shown e-marketing strategy is capable of providing a platform for the business enterprise. The research design uses quantitative methods which data was drawn from questionnaires responded by 142 respondents from 15 public universities in Malaysia. The data were analyzed based on descriptive and inferential statistical analysis using four types of statistical analysis method: the factor analysis, descriptive analysis, Pearson correlation test and multiple regression analysis. The results of the study suggested that publication policies and practices, as well as e-marketing, are the main contributors towards the performance of scholarly publishing in public universities